A régiók jelentősége a mai európai politikai életben : THE SIGNIFICANCE OF REGIONS IN TODAY’S EUROPEAN POLITICAL LIFE - Dr. Dömők, Csilla (Közép-Európai Közlemények, 2021)
A régiók nem csak a közelmúltban jelentek meg az európai politika színpadán, mint önálló szereplők, tevékenységüket már évtizedek óta jegyzik. Ennek középpontjában mindenekelőtt a régiók határokon átnyúló együttműködése áll, ezt egészítették ki a régiók transznacionális megállapodásaival, amelyek arra szolgáltak, hogy a nemzetállamok kormányaival valamint a nemzetközi szervezetekkel, különösképpen az Európa Tanáccsal és az Európai Közösséggel szemben érdekképviseletüket gyakorolják. Az utóbbi időben a régiók egyre energikusabban és követelőbben hívták fel magukra a figyelmet. Tevékenységük súlypontja jelenleg nyilvánvalóan az EU és az integrációs folyamatokon belül helyezkedik el. A régiók mint az EU-kontextus politikai tényezői igen sokrétű tevékenységet mutatnak fel, amelyek az „Európa régiói” megjelölésben foglalhatók össze. Az elnevezésből, mint sokszor használatos szlogenből azonban hiányzik egy egyértelmű és ugyanakkor közös megegyezéssel alapuló, elfogadott tartalom. Regions appeared as autonomous entities on the European political stage not only in recent years. The activity of regions has been recorded for decades. It focuses above all on the cross-border cooperation of regions, and was supplemented by the trans-national agreements of regions, which served to practice their representation against the governments of nation states as well as international organisations, in particular, the European Council and the European Community. Most recently, regions have drawn attention to their presence more and more and when doing so have found increasing attention. Their centre of activity is now obviously located within the EU and the integration processes. Regions as the political factors of the EU context show a wide range of activities that can be summarized under the label of ‘the regions of Europe’. The name, as a frequently used slogan, is lacking a clear and at the same time jointly agreed, accepted content. Regions and regionalism are rather flourishing in Europe. But what do regionalism and the expression Europe of regions exactly mean? There are many approaches to the question, the concept of cross-border interregionality between the Member States of the European Union, or the effort to make regions the basic building blocks of European integration instead of states, and the objective to introduce a three-tier structure to the European Union which would extend the already existing tiers of the European Union and the Member States with a third one, the territorial units within nation states. The first approach has long been adopted, the second approach is rather utopian. The third one is subject to fierce debates: a three-tier European Union with European, nation state and regional levels.